High performance SONOS flash memory with in-situ silicon nanocrystals embedded in silicon nitride charge trapping layer. (February 2018) - Lim, Jae-Gab; Yang, Seung-Dong; Yun, Ho-Jin; Jung, Jun-Kyo; Park, Jung-Hyun; Lim, Chan; Cho, Gyu-seok; Park, Seong-gye; Huh, Chul; Lee, Hi-Deok; Lee, Ga-Won
Abstract: In this paper, SONOS-type flash memory device with highly improved charge-trapping efficiency is suggested by using silicon nanocrystals (Si-NCs) embedded in silicon nitride (SiNX ) charge trapping layer. The Si-NCs were in-situ grown by PECVD without additional post annealing process. The fabricated device shows high program/erase speed and retention property which is suitable for multi-level cell (MLC) application. Excellent performance and reliability for MLC are demonstrated with large memory window of ∼8.5 V and superior retention characteristics of 7% charge loss for 10 years. High resolution transmission electron microscopy image confirms the Si-NC formation and the size is around 1–2 nm which can be verified again in X-ray photoelectron spectroscopy (XPS) where pure Si bonds increase. Besides, XPS analysis implies that more nitrogen atoms make stable bonds at the regular lattice point. Photoluminescence spectra results also illustrate that Si-NCs formation in SiNx is an effective method to form deep trap states.